Microencapsulação de hidrolisados de subproduto do processamento de frango para suplementação de ração para alevinos de tilápia do Nilo (Oreochromis niloticus) - Ogava, Luci Emi (2023)
Aquaculture, especially the farming of tilapia, has grown faster than other industries, and along with it, the demand for inputs, where feed accounts for more than half of production costs. Due to its high volume and potential impact on environmental issues, chicken waste has attracted particular interest. Its valorization would also result in cost savings. Protein residues can be hydrolyzed to produce smaller bioactive peptides that were inactive in the original chain and may lose their activity when they come into contact with the gastric enzymes of the organism that eats them. Encapsulation, a method that incorporates and safeguards the target molecule, can reduce a loss of activity, however it lacks in vivo experiments and process studies. Based on this backdrop, the current work was structured so that chapter I presents the state of the art where the main issues concerning the theme are contextualized. The chapter II talks about the main nutritional properties of the hydrolyzate of poultry viscera that meet the needs of Nile tilapia. These properties include protein and amino acid content, lipid profile, minerals, water activity, color, calorific value, and functional properties. and activities that fight free radicals and bacteria. In Chapter III, the effects of feeding Nile tilapia fingerlings chicken viscera hydrolyzate encapsulated with maltodextrin, gum arabic, and soy protein isolate are examined in relation to zootechnical performance, liver, muscle, and intestine histology, as well as viscerosomatic index. Color, size, surface charge potential of the particle, functional groups, and scanning electromicrography were used to manufacture and describe the capsules. The feed with 3% inclusion of encapsulated hydrolyzate had 40% crude protein and 3500 kcal/kg of digestible energy. There were three treatments with five repetitions: feed with maltodextrin encapsulation (MD), gum arabic (GA), soy protein isolate (IS), and viscera hydrolyzate as the control (CO). For the zootechnical performance, about 300 Nile tilapia fingerlings (each about 8g) were put into 20 tanks. After 30 days of getting six feedings a day and water quality monitoring, the final weight, weight gain, apparent feed conversion, protein efficiency rate, specific growth rate, total length, survival, gut length, hepatosomatic index, viscerosomatic index, and visceral fat index were assessed. According to the literature consulted in the evaluated qualities, the hydrolyzate of chicken viscera provided indexes and percentages optimal for the needs of Nile tilapia, including good antioxidant activity and absence of antibacterial activity. The scanning electron micrograph, the surface charge, the size, and the functional groups of the microcapsules all showed that the encapsulation was made by the wall materials. When compared to CO, the zootechnical performance showed a statistically significant difference with worse averages for the gum arabic treatment and no statistically significant difference between the IS and MD treatments. Therefore, those enclosed in IS and MD were better suited for usage in fingerling Nile tilapia.